Turkey: Greater Prosperity with Social Justice - World Bank (Washington, DC, 2013)
These policy notes are intended as background for initial discussions between the new Government and the World Bank about the development strategy for Turkey, and the possible support the World Bank could bring to implement that strategy. This paper presents recent work on specific sectors where action by the government would be needed. The main points in each note are outlined here: Strict fiscal management is key to full realization of the twin objectives of low inflation and steady growth in a setting of a gradually diminishing public debt burden. More effective government is the road to permanent macroeconomic stability and better delivery of public services under conditions of fiscal austerity. Fighting corruption is vital to ensuring that the government delivers effective services. While extreme poverty (US$1 a day) remains very low in Turkey, both urban food poverty and economic vulnerability are significant and have grown recently. Turkey has made unprecedented strides in the basic education program launched in 1997. Now the twin challenges are to increase gradually the share of GDP dedicated to education while still accepting that not all improvements in education can be afforded at once. Turkey ranks far behind most middle income countries in terms of health status. To meet the objective of improving the health status of the population, fundamental and systemic changes will be required in the ways that health care is financed, organized, and managed. Revitalizing the economy and further improving competitiveness require continued attention to the financial sector. Business was badly affected by the 2001 crisis, and although now exhibiting signs of growth, requires selective assistance to recover fully with the ability to compete in the future. Small and medium-sized enterprises (SMEs) should drive the creation of productive employment opportunities. Accelerating privatization is important for strengthening the credibility of the reform program and for supporting private sector development. Turkey is highly vulnerable to natural disasters, especially earthquakes and floods. Effective mitigation and preparedness can significantly reduce the risk of large economic and social costs. In recent decades, agriculture and other rural economic activities have failed to live up to their potential as contributors to growth, rural employment, and rural welfare. Telecommunications can be an important driver of technological change and economic growth for Turkey. transformation of the electricity and gas sectors to competitive private energy markets aims to decrease costs and risks currently borne by the government by attracting private capital. Increasing the efficiency of Turkey's transport sector will contribute to economic growth, environmental sustainability and poverty alleviation. Effective decentralization through greater empowerment of municipalities is key to improving services. Reform of the administration of justice will help ensure that justice is not denied by being delayed. Bringing civil society into development decisions will lead to more effective implementation of programs and meaningful results. A greater emphasis on transparency and participation must be combined with more readily available and consistent information.